2017
DOI: 10.1155/2017/6463139
|View full text |Cite
|
Sign up to set email alerts
|

Sapium ellipticum(Hochst.) Pax Ethanol Leaf Extract Maintains Lipid Homeostasis in Streptozotocin-Induced Diabetic Rats

Abstract: Dyslipidemia is a common metabolic disorder especially in diabetes mellitus (DM). In this study, the ability of Sapium ellipticum (SE) leaf extract to restore lipid homeostasis in streptozotocin-induced diabetes was examined. DM was induced in experimental rats (Wistar strains) using single intraperitoneal dose (55 mg/kg body weight {BW}) of streptozotocin (STZ). Treatment of diabetic rats with SE was oral (p.o), at doses of 400 and 800 mg kg−1 BW, twice daily at 8 h interval for 21 days. Lipid parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
3
1
0
Order By: Relevance
“…Diabetic rats had a significant elevation in plasma TAG and LDL-C levels, while HDL-C levels were significantly reduced when compared to control rats. These findings are consistent with results of Ighodaro et al [ 23 ] and Zhang et al [ 24 ] in which the authors reported significant elevations in total cholesterol, TAG, HDL-C, and LDL-C of STZ-treated rats, and with our previous results that the plasma concentration of insulin was significantly reduced in diabetic rats, which led to hyperglycemia with a high percentage of HbA1C [ 13 ]. Alternatively, TQ significantly improved the plasma levels of TAG, LDL-C, and HDL-C in the diabetic + TQ group in relation to the diabetic group.…”
Section: Discussionsupporting
confidence: 93%
“…Diabetic rats had a significant elevation in plasma TAG and LDL-C levels, while HDL-C levels were significantly reduced when compared to control rats. These findings are consistent with results of Ighodaro et al [ 23 ] and Zhang et al [ 24 ] in which the authors reported significant elevations in total cholesterol, TAG, HDL-C, and LDL-C of STZ-treated rats, and with our previous results that the plasma concentration of insulin was significantly reduced in diabetic rats, which led to hyperglycemia with a high percentage of HbA1C [ 13 ]. Alternatively, TQ significantly improved the plasma levels of TAG, LDL-C, and HDL-C in the diabetic + TQ group in relation to the diabetic group.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with our results and could be due to an increased non-enzymatic glycation of HDL-C resulting in its increased clearance [40]. While our study did not observe a significant improvement of HDL level after treatment with the plant extracts alone and in combination, the finding is however in agreement with the study of Ighodaro et al [41]. This emphasizes the need for long- term research in order to ascertain the lipid-lowering mechanism of action of the medicinal plants as potential drug candidates.…”
Section: Discussionsupporting
confidence: 94%
“…Administration of alloxan could have resulted in leakage of these enzymes from the liver and some other tissues into circulation, indicating the injury of these tissues. The effect of SPA on liver enzyme markers is in agreement with several other studies on medicinal plant effects in diabetic rats [27,28].…”
Section: Discussionsupporting
confidence: 91%
“…Akinloye and Solanke [25] reported a marked reduction in serum triglyceride, total cholesterol, high-density lipoprotein, and low-density lipoprotein cholesterol in alloxan-induced hyperglycemic rats treated with Pigeon pea methanol extract. Sapium ellipticum leaf ethanol extract has been reported to maintain lipid homeostasis in streptozocin-induced diabetic rats [27].…”
Section: Discussionmentioning
confidence: 99%